The Violation of Human Rights during the Bakassi Peninsula Conflict from 1965 to 2013 - Stephen Achuo Kpwa (Universitas Jember, 2023)
The military skirmishes over the Bakassi peninsula between Cameroon and Nigeria was as a result of the vestiges of colonialism and the discovery of large deposits of natural resources in the area. This study explores the violations of human rights in the Bakassi peninsula during the Bakassi conflict. The study mainly explores how, when and where these human rights abuses were committed, and to a lesser extent why and who committed these abuses. The study adopts the qualitative research method and from it, historical consolidation and content analyses in terms of data collection. The use of secondary data, applied with the thematic approach in this study brings to the fore that there were lots of human rights violations during the Bakassi conflict in the Bakassi peninsula. This study could be utilised by researchers and policy makers to understand human rights trends in the Bakassi peninsula area. Keywords: Cameroon, Nigeria, Violations, Human Rights, Bakassi Peninsula Conflict